"a carefully weighed plan with adequate safeguards for us": Economic Policy and the Coordination of Australian‐US Approaches to Japanese Aggression, 1939‐41. (12th July 2020) - Cuffe, Honae
Abstract : The historical narrative of Australia's foreign and defence policy‐making during the Pacific War tends to foreground the years 1941–42, characterising them as the turning point when the government realised that Britain alone could no longer protect Australia's regional security interests and turned to the United States of America for its salvation. This article makes a contribution to the alternative view, arguing that Australia was looking to the US well before Prime Minister John Curtin's famous "looks to America" proclamation. It does so with a focus on Australia's thinking and policy towards the engagement of the US in the years 1939‐41, arguing that the coordination of its economic policy with the US, rather than seeking insight into high‐level strategic planning, offered the nation the greatest opportunity to tie its security interests in the Asia‐Pacific region with those of the US. In exploring the role of economic policy in Australia's preparation for war, this article offers new insight into the maturation of Australia's foreign policy apparatus.